Phenoxazine-based panchromatic organic sensitizers for dye-sensitized solar cells. (May 2015) - Li, Jiajia; Yang, Xichuan; Cheng, Ming; Wang, Mei; Sun, Licheng
Abstract: A series of metal-free organic dyesLJJ101 –LJJ103 composed of phenoxazine unit and indolinum carboxyl acid derivative have been synthesized for dye-sensitized solar cells. A systematic investigation has been conducted for the photology and electrochemistry properties of dyesLJJ101 –LJJ103 . Panchromatic spectra responses for all the three dyes have been obtained and extended to about 800 nm in near-infrared region. Compared toLJJ101, the introduction of thiophene and squaraine unit causes a red-shift absorption response forLJJ102 andLJJ103, respectively. When applied in dye-sensitized solar cells under AM 1.5 illumination, the device sensitized byLJJ103 yields the best conversion efficiency of 5.1% with a short-circuit photocurrent density of 13.7 mA/cm 2, an open-circuit photovoltage of 502 mV and a ﬁll factor of 74.0%. Graphical abstract: Highlights: Three new dyes based on phenoxazine unit and indolinum carboxyl acid derivative were synthesized. All dyes exhibited panchromatic response both in CH2 Cl2 solution and on TiO2 film. A best overall conversion efficiency of 5.1% was obtained for DSSCs withLJJ103.